Blockene: A High-throughput Blockchain Over Mobile Devices - Satija, Sambhav; Mehra, Apurv; Singanamalla, Sudheesh; Grover, Karan; Sivathanu, Muthian; Chandran, Nishanth; Gupta, Divya; Lokam, Satya (OSDI 2020, 2020)
We introduce Blockene, a blockchain that reduces resource usage at member nodes by orders of magnitude, requiring only a smartphone to participate in block validation and consensus. Despite being lightweight, Blockene provides high throughput and scales to millions of participants. Blockene consumes negligible battery and data in smartphones, enabling millions of users to participate in the blockchain without incentives, to secure transactions with their collective honesty. Blockene achieves these properties with a novel split-trust design based on delegating storage and gossip to untrusted nodes. We demonstrate, with a prototype implementation, that Blockene provides a throughput of more than 1000 transactions per second, and can run with very low resource usage on smartphones, pointing to a new paradigm for building trustworthy, decentralized applications.